Penerapan Model Pembelajaran Bahasa Inggris Kontekstual untuk Meningkatkan Penguasaan Kosakata Fungsional Siswa SMK Kelas X - Yulita Halim (INDO PUBLISHING, 2025)
This study aims to improve the functional English vocabulary mastery of tenth-grade vocational students through the implementation of contextual learning models. The research was motivated by students’ limited ability to understand and use vocabulary relevant to real workplace situations. The method used was Classroom Action Research (CAR), conducted in two cycles consisting of planning, action, observation, and reflection. The subjects were 30 tenth-grade students from various departments at SMK Negeri 1 Tapaktuan. Learning materials were designed based on cross-professional workplace communication contexts, such as greeting, instruction, report, and complaint. Evaluation was based on four vocabulary mastery indicators: form, meaning, pronunciation, and usage. The results showed a significant improvement in all indicators, with classical mastery increasing from 63.3% in cycle I to 86.7% in cycle II. These findings indicate that contextual English learning is effective in enhancing vocational students’ functional vocabulary and can serve as a relevant instructional strategy aligned with vocational education needs.